Poster 114: Lower Extremity Injury Following Return to Sport from Concussion: A Systematic Review. Issue 7 (30th July 2022) - Jildeh, Toufic; Buckley, Patrick; Abbas, Muhammad; Hedge, Yash; Okoroha, Kelechi; Castle, Joshua
Objectives: To examine the current body of research and determine whether there is an increased risk for LE musculoskeletal injury following a concussion and identify populations at an increased risk. Methods: A systematic review of the literature from January 1, 2000 to September 30, 2020 was performed using MEDLINE and PubMed databases. Key words included concussion, athlete, lower extremity injury, and return to sport . Inclusion criteria required original research articles written in English language examining the rate of LE injuries following a diagnosed concussion. Data extracted from each study included number of subjects, age, sex, sport played, level of play, odds ratio (OR) of injury, and number of concussions per athlete. Results: A total of 13 studies involving 4, 349 athletes (88.1% male; mean age 19.8 years) met inclusion criteria. Athletes were classified as either high school (46.1%), collegiate (17.0%), or professional (36.9%). Four studies demonstrated an increased risk of LE injury within 90 days of a diagnosed concussion (OR 3.44, 95% CI 2.99-4.42) and 7 studies revealed an elevated risk of injury within one year of concussion (OR 1.85, 95% CI 1.73-2.84). Professional and college athletes demonstrated an increased risk (OR 2.49, 95% CI 2.40-2.72; OR 2.00, 95% CI 1.96-2.16, respectively) compared to high school athletes (OR 0.97, 95% CI 0.89-1.05). A stepwise increase in risk of sustaining a LE injury was observed with multiple concussions, with increasing risk observed from 2+ (OR 2.29, 95% CI 1.85-2.83) to 3+ career concussions (OR 2.86, 95% CI 2.36-3.48). Conclusions: An increased incidence of LE injuries was observed at 90-days and one year following the diagnosis of a concussion. Higher levels of competition, such as at the collegiate and professional level, resulted in an increased risk of sustaining a subsequent LE injury following a diagnosed concussion. These results suggest an at-risk population which may benefit from injury prevention methods following a concussion. Table 1. Study Characteristics Table 2. Odds ratio of suffering lower extremity injury within 90 days from a concussion Table 3. Odds ratio of suffering lower extremity injury within one year of concussion Table 5. Comparing lower extremity injury risk following concussion by level of competition